Active brazing filler metal for sealing sapphire and kovar alloy and preparation method of active brazing filler metal
By adopting a specific composition of active solder and advanced preparation process, the problem of insufficient sealing strength and airtightness in the connection between sapphire and coval alloy is solved, and the sealing effect of high strength, high airtightness and long life is achieved.
Patent Information
- Application Number
- CN202411552375.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to achieve high strength, high airtightness and long-life sealing in the connection between sapphire and covaler alloy. Traditional active solder materials are difficult to form into foil due to their high brittleness and difficult processing.
Using active solder materials with Cu content of 25.0-27.5 wt%, Ti content of 1.0-6.0 wt%, Al content of 1.0-5.0 wt%, B content of 0.1-1.0 wt%, and rare earth element RE, powder making and machinery are made by vacuum air atomization Ball milling and other processes produce foils with good wetting and spreading properties.
It achieves good sealing between sapphire and covaler alloy, and does not prone to cracking after the device is sealed, has excellent airtightness, high yield, and can be processed to foils with a thickness of less than 0.1mm.
Smart Images

Figure HDA0005115426320000011 
Figure HDA0005115426320000012
Abstract
Description
Technical Field
[0001] The invention relates to a medium-temperature active solder and a preparation method thereof, and in particular to an active solder for sealing sapphire and kovar alloy and a preparation method thereof. Background Art
[0002] Sapphire is a single crystal aluminum oxide with high hardness, high strength, high thermal stability and excellent wave transmittance. Sapphire has a transmittance of more than 83% in the wavelength range of 350-3000nm. It is an optical material with excellent performance and is widely used in aerospace, electronic devices and other fields. In the electronics industry, sapphire is often used as a transparent LED packaging substrate, and traditional soft soldering can meet the requirements. The connection between sapphire and other metal components in the infrared detector Dewar assembly requires bonding and metallization followed by welding. For some special application scenarios, such as sapphire as an aircraft light window, the surface temperature can reach 400-600℃ when in use, so the sealing of the aircraft light window requires a higher temperature. As a ceramic material, sapphire has a room temperature thermal expansion coefficient of only 4.9×10 -6 / ℃, which is lower than most metal materials. If the temperature of the connection with the metal is too high, a large thermal stress will be formed on one side of the sapphire. As a single crystal material, sapphire has poor toughness and is prone to cracking due to large thermal stress. This means that the sealing of sapphire on high-speed aircraft can only select metal base materials from limited low-expansion metals, such as Kovar alloy. The connection between sapphire and Kovar alloy was mechanically connected or bonded in the early days. The mechanical connection structure is simple, but sapphire is brittle, hole processing is difficult, and cracks are easy to occur. The bonding method is simple, but the airtightness is not ideal and the life is short. Therefore, the two connection methods are difficult to meet the connection requirements of high strength, high airtightness and long life between sapphire and Kovar. Through the brazing method, a joint with good airtightness can be obtained, and the stress can be regulated by the process. The joint is not easy to age and can be used to replace mechanical connection and bonding. Traditional silver-based active brazing alloys mostly melt and cast the raw materials in vacuum, and are processed into foils by rolling. However, due to the precipitation of brittle intermetallic compounds during the casting solidification process, the material is prone to cracking during subsequent plastic processing, and the thickness is difficult to process to less than 0.1mm. Summary of the invention
[0003] The main purpose of the present invention is to provide an active solder for sealing sapphire and Kovar alloy, which improves the problems of traditional active solders being brittle and difficult to be processed into foil. The active solder has a moderate melting temperature and good fluidity and wettability on the sapphire substrate, which can meet the sealing requirements of sapphire and Kovar alloy in devices such as aircraft optical windows, and improve the device packaging yield and service reliability.
[0004] Another object of the present invention is to provide a method for preparing the above-mentioned active solder, which has a short process flow and a high yield rate, effectively improves traditional casting defects, coarse dendrites inside the alloy and brittle intermetallic compounds, obtains a structure with fine grain size and uniform composition, improves the elongation of the alloy, and can be processed into foil with a thickness of less than 0.1 mm.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] An active solder for sealing sapphire and kovar alloy, the solder comprises: 25.0-27.5wt% Cu, 1.0-6.0wt% Ti, 1.0-5.0wt% Al, 0.1-1.0wt% B, 0.1-0.5wt% rare earth element RE, RE is one or more of La, Ce, Sc, Pr, Nd and Er, and the balance is Ag.
[0007] The active solder for sealing sapphire and Kovar alloy as described above, preferably, has a composition of: Cu content 26.5-27.5wt%, Ti content 3.5-4.5wt%, Al content 1.0-2.0wt%, B content 0.1-0.2wt%, rare earth element RE content 0.3-0.5wt%, RE is one or more of La, Ce, Sc, Pr, Nd and Er, and the balance is Ag.
[0008] As described above, the active solder for sealing sapphire and Kovar alloy is preferably in the form of foil with a thickness of 0.05-0.2 mm.
[0009] Adding appropriate amounts of Ti, B and Al elements to the active solder of the present invention can effectively enhance the activity of the solder, so that it has good wettability and spreadability on the sapphire substrate. The addition amount of the above elements should not be too high. If it is higher than the above range, the melting temperature of the solder will be too high, the grains inside the parent material will grow excessively, the strength of the grain boundaries will be reduced at high temperatures, and even rheology will occur, resulting in the formation of intergranular cracks, causing problems such as poor brazing sealing.
[0010] On the other hand, the present invention provides a method for preparing the active solder as described above, comprising the following steps:
[0011] (1) Weigh several raw materials according to mass percentage: Cu content 25.0-27.0wt%, Ti content 1.0-6.0wt%, Al content 1.0-5.0wt%, B content 0.1-1.0wt%, rare earth element RE content 0.1-0.5wt%, RE is one or more of La, Ce, Sc, Pr, Nd and Er, and the balance is Ag.
[0012] (2) The weighed Ag, Cu, Ti, and Al metal raw materials are placed in a crucible in a vacuum gas atomization powder making device, heated to 1200-1300° C. for vacuum melting, and after the metals are completely melted, gas atomization powder making is performed to obtain Ag-Cu-Ti-Al alloy powder.
[0013] (3) The B powder and rare earth element RE powder weighed in step (1) and the Ag-Cu-Ti-Al alloy powder obtained in step (2) are placed in a ball mill for mechanical ball milling.
[0014] (4) The alloy powder obtained in step (3) is subjected to vacuum pressure sintering, rough rolling, intermediate annealing, and finish rolling to form a foil.
[0015] In the preparation method as described above, preferably, in the step (1), the purity of Cu, Al and Ag in the raw materials is 99.99%, the purity of Ti is 99.9%, the above raw materials are one or more of block, flake and granular forms, B is an amorphous boron powder with a purity of ≥96wt.%, the particle size of the boron powder is 100-200 mesh, and the water content of the boron powder is ≤0.1wt.%.
[0016] In the preparation method described above, preferably, in step (2), the atomizing gas pressure is 0.5-1.5 MPa, and the working vacuum degree is (6.5-6.7)×10 -1 Pa, atomizing gas flow rate is 15-30Nm 3 / min, the protective atmosphere is argon or nitrogen.
[0017] In the preparation method as described above, preferably, in the step (3), the grinding balls are agate balls, the ball-to-material ratio is 5-10:1, the ball milling speed is 100-200 rad / min, and the ball milling time is 2 hours to 4 hours.
[0018] In the preparation method described above, preferably, in step (4), the vacuum sintering pressure is 35MPa to 50MPa, and the vacuum degree is 1.0×10 -3 Pa-1.0×10 -4 Pa, the sintering temperature is 700℃-750℃.
[0019] In the preparation method as described above, preferably, in the step (4), the single-pass rolling deformation rate is 15-25%, the total deformation rate is less than 90%, the intermediate annealing temperature is 550°C-580°C, and the holding time is 60min-120min.
[0020] The beneficial effects of the present invention are as follows:
[0021] (1) The active solder of the present invention has good matching of thermal expansion coefficient with sapphire, and is suitable for direct connection between sapphire and Kovar alloy. The device is not prone to cracking after sealing, and has excellent air tightness.
[0022] (2) The active solder component of the present invention contains the active element Ti. During the brazing process, the Ti element can diffuse into the sapphire and the Kovar matrix, reacting at the interface to form TiO and TiFe 2 The addition of Al to the solder can react with Ag to generate an enriched phase at the sapphire interface during brazing, which forms a strong interface bond between the sapphire and the solder alloy, thereby improving the shear strength of the joint. The addition of B can generate a TiB reinforcing phase with Ti, and a small amount of intermetallic compounds can effectively strengthen the joint connection area. The addition of RE can refine the solder grains, improve the plasticity and impact resistance of the solder joint, match the mechanical properties of the solder and the parent material, and effectively improve the comprehensive performance of the joint sealing.
[0023] (3) The powder obtained by the vacuum gas atomization powder making method of the present invention has high sphericity, low oxygen content, simple process, good powder fluidity, and is convenient for large-scale industrial production. Compared with the traditional melting and casting technology, it has fine structure, small component segregation, and can expand the solid solubility of elements.
[0024] (4) The intermediate treatment process of the present invention can refine solder grains, make the material structure and composition uniform, eliminate structural defects, reduce segregation, reduce deformation and crack tendency, stabilize strip size, reduce material hardness, and improve material processing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a photo of the active solder foil prepared in Example 1.
[0026] Figure 2 This is a microstructure photograph of the sapphire / Kovar alloy bonding interface encapsulated by the active solder prepared in Example 1. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.
[0028] Embodiment 1:
[0029] (1) Weigh 130 g of Cu block with a purity of 99.99%, 5 g of Al sheet, 339.5 g of Ag block, 22.5 g of Ti sheet with a purity of 99.9%, 0.5 g of amorphous B powder with a powder particle size of 200 mesh, and 2.5 g of La powder.
[0030] (2) The weighed Ag, Cu, Ti, and Al metal raw materials were placed in a crucible in a vacuum gas atomization powder making device and heated to 1250°C for vacuum melting. After the metals were completely melted, gas atomization powder making was performed. The atomization gas pressure was 0.5 MPa and the working vacuum degree was 6.50×10 -1 Pa, atomizing gas flow rate is 15Nm 3 / min, with argon as the protective atmosphere, to obtain Ag-Cu-Ti-Al alloy powder.
[0031] (3) The B powder, rare earth element RE powder and Ag-Cu-Ti-Al alloy powder weighed in step (1) and obtained in step (2) are placed in the tank of a ball mill for mechanical ball milling. The grinding balls are agate balls, the ball-to-material ratio is 10:1, the ball milling speed is 150 rad / min, and the ball milling time is 3 hours.
[0032] (4) The alloy powder obtained in step (3) is subjected to vacuum pressure sintering, the vacuum sintering pressure is 35 MPa, the vacuum degree is 1.0×10 -3 Pa, sintering temperature is 750℃. The diameter of sintered ingot is 80mm. The ingot is roughly rolled into plate. The intermediate annealing temperature is 580℃, and the holding time is 80min. After intermediate annealing, it is finely rolled into foil strip. The single-pass rolling deformation rate is 15%, and the total deformation rate is less than 90%, and the foil strip with a thickness of 0.15mm is obtained.
[0033] The prepared silver-based active solder strip is shown in the following figure. Figure 1 As shown, the surface of the strip is bright and smooth, without defects such as cracking and overlapping, and has good dimensional consistency.
[0034] The microstructure of the interface between sapphire and Kovar alloy is shown in the figure. Figure 2 As shown in the figure, it can be seen that sapphire is well bonded to the Kovar alloy matrix without defects such as holes and gaps.
[0035] Embodiment 2:
[0036] (1) Weigh 125 g of 99.99% pure Cu block, 25 g of Al sheet, 339.5 g of Ag block, 5 g of 99.9% pure Ti sheet, 2.5 g of 200-mesh amorphous B powder, and 0.5 g of Ce powder.
[0037] (2) The weighed Ag, Cu, Ti, and Al metal raw materials were placed in a crucible in a vacuum gas atomization powder making device and heated to 1200°C for vacuum melting. After the metals were completely melted, gas atomization powder making was performed. The atomization gas pressure was 0.5 MPa and the working vacuum degree was 6.60×10 -1 Pa, atomizing gas flow rate is 20Nm 3 / min, with argon as the protective atmosphere, to obtain Ag-Cu-Ti-Al alloy powder.
[0038] (3) The B powder, rare earth element RE powder and Ag-Cu-Ti-Al alloy powder weighed in step (1) and obtained in step (2) are placed in the tank of a ball mill for mechanical ball milling. The grinding balls are agate balls, the ball-to-material ratio is 10:1, the ball milling speed is 100 rad / min, and the ball milling time is 4 hours.
[0039] (4) The alloy powder obtained in step (3) is subjected to vacuum pressure sintering, the vacuum sintering pressure is 30 MPa, the vacuum degree is 1.0×10 -3 Pa, sintering temperature is 700℃, sintered ingot diameter is 80mm. The ingot is roughly rolled into a plate. The intermediate annealing temperature is 550℃, and the holding time is 60min. After intermediate annealing, it is finely rolled into a foil strip, the single-pass rolling deformation rate is 20%, the total deformation rate is less than 90%, and a foil strip with a thickness of 0.05mm is obtained.
[0040] Embodiment 3:
[0041] (1) Weigh 135 g of 99.99% pure Cu block, 15 g of Al sheet, 340.5 g of Ag block, 5 g of 99.9% pure Ti particles, 2.5 g of 200-mesh amorphous B powder, 1 g of Nd powder, and 1 g of Er powder.
[0042] (2) The weighed Ag, Cu, Ti, and Al metal raw materials were placed in a crucible in a vacuum gas atomization powder making device and heated to 1300°C for vacuum melting. After the metals were completely melted, gas atomization powder making was performed. The atomization gas pressure was 1.0 MPa and the working vacuum degree was 6.60×10 -1 Pa, atomizing gas flow rate is 25Nm 3 / min, with nitrogen as the protective atmosphere, to obtain Ag-Cu-Ti-Al alloy powder.
[0043] (3) The B powder, rare earth element RE powder and Ag-Cu-Ti-Al alloy powder weighed in step (1) and obtained in step (2) are placed in the tank of a ball mill for mechanical ball milling. The grinding balls are agate balls, the ball-to-material ratio is 8:1, the ball milling speed is 150 rad / min, and the ball milling time is 2 hours.
[0044] (4) The alloy powder obtained in step (3) is subjected to vacuum pressure sintering, the vacuum sintering pressure is 40 MPa, the vacuum degree is 1.0×10 -4Pa, sintering temperature is 750℃, sintered ingot diameter is 80mm. The ingot is roughly rolled into a plate. The intermediate annealing temperature is 570℃, and the holding time is 120min. After intermediate annealing, it is finely rolled into foil strip, the single-pass rolling deformation rate is 15%, the total deformation rate is less than 90%, and the foil strip with a thickness of 0.15mm is obtained.
[0045] Embodiment 4:
[0046] (1) Weigh 127.5 g of 99.99% pure Cu sheet, 10 g of Al block, 344 g of Ag block, 15 g of 99.9% pure Ti sheet, 2.5 g of 200-mesh amorphous B powder, and 1 g of Sc powder.
[0047] (2) The weighed Ag, Cu, Ti, and Al metal raw materials were placed in a crucible in a vacuum gas atomization powder making device and heated to 1280°C for vacuum melting. After the metals were completely melted, gas atomization powder making was performed. The atomization gas pressure was 1.5 MPa and the working vacuum degree was 6.70×10 -1 Pa, atomizing gas flow rate is 30Nm 3 / min, with nitrogen as the protective atmosphere, to obtain Ag-Cu-Ti-Al alloy powder.
[0048] (3) The B powder, rare earth element RE powder and Ag-Cu-Ti-Al alloy powder weighed in step (1) and obtained in step (2) are placed in the tank of a ball mill for mechanical ball milling. The grinding balls are agate balls, the ball-to-material ratio is 5:1, the ball milling speed is 200 rad / min, and the ball milling time is 3 hours.
[0049] (4) The alloy powder obtained in step (3) is subjected to vacuum pressure sintering, the vacuum sintering pressure is 50 MPa, the vacuum degree is 1.0×10 -4 Pa, sintering temperature is 720℃, sintered ingot diameter is 80mm. The ingot is roughly rolled into a plate. The intermediate annealing temperature is 550℃, and the holding time is 60min. After intermediate annealing, it is finely rolled into foil strip. The single-pass rolling deformation rate is 18%, and the total deformation rate is less than 90%, and a foil strip with a thickness of 0.1mm is obtained.
[0050] Experimental Example 1
[0051] The melting temperature of the active solders prepared in Examples 1 to 4 was tested respectively, and the sealing strength of the sapphire and the kovar alloy was tested after brazing. The results are shown in Table 1.
[0052] Table 1 Brazing performance test results of active solder prepared in Examples 1 to 4
[0053] Solid phase temperature ℃ Liquidus temperature ℃ Brazing rate % Sealing strengthMpa Example 1 751.8 770.5 99.6 130.9 Example 2 746.7 763.2 99.3 120.7 Example 3 758.4 775.1 99.5 124.2 Example 4 749.6 769.9 99.4 126.1
[0054] The above experimental results show that the active solder of the present invention can achieve good packaging of sapphire and kovar alloy. The soldering temperature is moderate, the packaging process is simple and efficient, the device is not prone to cracking after sealing, and the yield is high.
[0055] The above embodiments only cite some embodiments of the active solder for sealing sapphire and Kovar alloy and the preparation method thereof of the present invention. In the above technical scheme of the present invention: the contents of the alloy components Ag, Cu, Ti, Al, B, and RE can be freely selected within the prescribed range and are no longer listed here one by one. Therefore, the technical scheme contained in the above description should be regarded as illustrative rather than used to limit the protection scope of the patent application of the present invention.
Claims
1. An active solder for sealing sapphire and Kovar alloy, characterized in that: The solder has the following composition: Cu content 25.0-27.5wt%, Ti content 1.0-6.0wt%, Al content 1.0-5.0wt%, B content 0.1-1.0wt%, rare earth element RE content 0.1-0.5wt%, RE is one or more of La, Ce, Sc, Pr, Nd and Er, and the balance is Ag.
2. The active solder for sealing sapphire and Kovar alloy according to claim 1, characterized in that: The solder has the following composition: Cu content 26.5-27.5wt%, Ti content 3.5-4.5wt%, Al content 1.0-2.0wt%, B content 0.1-0.2wt%, rare earth element RE content 0.3-0.5wt%, RE is one or more of La, Ce, Sc, Pr, Nd and Er, and the balance is Ag.
3. The active solder for sealing sapphire and Kovar alloy according to claim 1 or 2, characterized in that: The solder is in the form of foil with a thickness of 0.05-0.2 mm.
4. The method for preparing the active solder for sealing sapphire and Kovar alloy according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: I. Weigh several raw materials according to the ratio; II. The weighed Ag, Cu, Ti, Al metal raw materials are placed in a crucible in a vacuum gas atomization powder making device, heated to 1200-1300 ° C for vacuum melting, and after the metal is completely melted, gas atomization powder is obtained to obtain Ag-Cu-Ti-A1 alloy powder; III. The B powder, the rare earth element RE powder weighed in step I and the Ag-Cu-Ti-Al alloy powder obtained in step II are placed in a ball mill tank for mechanical ball milling; IV. The alloy powder obtained in step III is subjected to vacuum pressure sintering, rough rolling, intermediate annealing, and finish rolling to form a foil.
5. The method according to claim 4, characterized in that In the step I, the purity of Cu, Al and Ag in the raw materials is 99.99%, and the purity of Ti is 99.9%, and the above raw materials are in block, flake or granular form; B is amorphous boron powder with a purity of ≥96wt.%, the particle size of the boron powder is 100-200 mesh, and the water content of the boron powder is ≤0.1wt.%.
6. The method according to claim 4, characterized in that In step II, the atomizing gas pressure is 0.5-1.5 MPa, and the working vacuum is (6.50-6.70)×10 -1 Pa, atomizing gas flow rate is 15-30Nm 3 / min, the protective atmosphere is argon or nitrogen.
7. The method according to claim 4, characterized in that In step III, the grinding balls are agate balls, the ball-to-material ratio is (5-10):1, the ball milling speed is 100-200 rad / min, and the ball milling time is 2 hours to 4 hours.
8. The method according to claim 4, characterized in that In step IV, the vacuum sintering pressure is 35MPa to 50MPa, and the vacuum degree is 1.0×10 -3 Pa-1.0×10 -4 Pa, the sintering temperature is 700℃-750℃.
9. The method according to any one of claims 4 to 8, characterized in that In step IV, the single-pass rolling deformation rate is 15-25%, the total deformation rate is less than 90%, the intermediate annealing temperature is 550° C.-580° C., and the holding time is 60 min-120 min.
Citation Information
Patent Citations
Solder for welding carbon / silicon carbide ceramic matrix composite material and titanium-aluminum-based alloy and soldering method
CN101786899A
Solder for connecting ceramics with kovar alloys
CN106312369A
Brazing filler metal for brazing 3D printing stainless steel and alumina ceramic and preparation and brazing method
CN106736034A
Ag-Cu-In-Sn-Ti alloy brazing filler material and preparation method thereof
CN108340094A
Method for brazing connection of AlN ceramic and Cu
CN113909608A
Cited By
Kovar alloy and ceramic welding composition and application thereof
CN119927499A
Rare earth silver copper alloy and preparation method and application thereof
CN120945245A
Lanthanum-containing silver alloy and preparation method and application thereof
CN120989450A
Sapphire-kovar alloy connector and welding method thereof
CN121649495A